Metamorphic evolution and $P$–$T$ path of the Posada Valley amphibolites: new insights on the Variscan high pressure metamorphism in NE Sardinia, Italy - Scodina, Massimo; Cruciani, Gabriele; Franceschelli, Marcello (Comptes Rendus. Géoscience, 2021)
The Posada Valley amphibolites in the inner zone of Variscan Sardinia are characterized by garnet porphyroblasts containing epidote, titanite, quartz, clinopyroxene, amphibole, and plagioclase concentrated in the garnet core. The matrix is made up of amphibole and plagioclase and fine-grained clinopyroxene and plagioclase. The amphibolites recorded an HP stage, a metamorphic re-equilibration, and a third stage under the greenschist facies. $P$–$T$ conditions of stage I (530–650 °C/0.9–1.3 GPa for garnet core and 570–690 °C/1.0–1.4 GPa for garnet rim) were obtained by $P$–$T$ pseudosection modelling. The $P$–$T$ conditions for stage 2 ($T=$ 600–700 °C/$P=$ 0.5–0.8 GPa) were obtained by applying the same approach to the most retrogressed samples. The Posada Valley amphibolites underwent a cooler evolution, with a thermal peak lower than that recorded by the northward eclogites from the high-grade metamorphic complex of Sardinia.The proposed geodynamic scenario starts with the subduction of oceanic crust under the peri-Gondwanan terrane in Upper Devonian. The Posada Valley amphibolites were subducted up to maximum depths of 50 km. Subsequently, they reached the subduction channel or were detached from the slab before the eclogite facies conditions were reached.